Keterlaksanaan Pembelajaran Bola Voli Secara Daring Pada SMA Kelas X Se-Kecamatan Majalaya - Fauzia Ramadhanti Azahrah; Rolly Afrinaldi; Fahrudin Fahrudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
This study aims to determine the implementation of online volleyball learning in class X high school. Based on the results of the study, online volleyball learning in class X high school is still not fully implemented. This research is a quantitative descriptive study with percentages. The subjects of this study were 35 high school students of Class X in Majalaya District, Karawang Regency. The instrument used is an online questionnaire with Google Forms. The results showed that the 4 Factors of Implementation of Online Volleyball Learning at SMA Class X in Majalaya Sub-district, Karawang Regency in the learning planning carried out 79.36%, the learning process carried out 95.81%, assignments were carried out 96%, and obstacles were implemented 82.86% . Overall, 88.51% have been implemented and 11.49% have not been implemented.